Paternal emotional deficiency in children - Souad AIT HABOUCHE (Social Sciences Journal, 1970)
In most cases, the child lives with the family, which consists of a group of individuals connected by the blood association and living under one roof. The family is now composed of the father, mother and brothers, because the family is currently mostly nuclear. This has led to major problems in dealing with the child This is called parental deprivation. It is also a denial of authority. It has a profound effect on the psyche of the child. It is also easy for us to diagnose the problem of parental deprivation from the first encounter with the child. , And this is what we are trying to clarify through this work